A New Route to Pyrano[3,2-a]carbazole Ring Systems and Annulated Derivatives Thereof - Chattopadhyay, Shital K.; Ghosh, Debalina; Mondal, Poulomi; Ghosh, Sanjay K. (Synthesis, 2012)
A new protocol based on sequential applications of Claisen rearrangement, olefin isomerisation, ring-closing diene/ enyne metathesis and Diels–Alder reaction has been developed to access pyrano[3,2-a]carbazole and annulated derivatives thereof.
Keywords: heterocycles; metathesis; rearrangement; Diels–Alder reaction; isomerisation